Bridging theory, policy, and practice: Stakeholder engagement in Ghana's NPEC - Richard Lionel Gorni; Asep Suryana; Eka Prihatin (Inovasi Kurikulum, 2024)
Ghana's education system is transforming significantly by implementing the National Pre-Tertiary Education Curriculum Framework (NPECF), emphasizing critical thinking and problem-solving skills over traditional rote learning. Translating these ambitious policy goals into effective classroom practices within a centralized system presents challenges. This research addresses this challenge through stakeholder analysis, examining how the involvement of policymakers, educators, parents, and local communities can bridge the gap between NPECF's theoretical ideals and practical classroom application. The research identifies potential roadblocks and opportunities for successful curriculum adoption by analyzing these diverse perspectives. Understanding the interactions and influences among policymakers, teachers, parents, and communities is crucial for transitioning smoothly from rote learning to a student-centered approach. This analysis highlights areas where stakeholders might need additional support or resources to embrace the new curriculum effectively. Ultimately, the findings can inform future educational reforms in Ghana and similar contexts, paving the way for a more effective and engaging learning experience for all students.   Abstrak Sistem pendidikan Ghana sedang mengalami transformasi signifikan dengan implementasi National Pre-Tertiary Education Curriculum Framework (NPECF) yang menekankan kemampuan berpikir kritis dan keterampilan pemecahan masalah - lebih dari pembelajaran tradisional. Tetapi menerjemahkan tujuan kebijakan ambisius ini ke dalam praktik kelas yang efektif dalam sistem terpusat - pada gilirannya menyajikan tantangan. Penelitian ini bertujuan untuk menangani tantangan ini melalui analisis terhadap pemangku kepentingan, memeriksa bagaimana keterlibatan pembuat kebijakan, pendidik, orang tua, dan komunitas lokal dapat menjembatani kesenjangan antara cita-cita teoritis NPECF dengan aplikasi kelas praktis. Melalui analisis terhadap perspektif yang beragam ini, penelitian ini mengidentifikasi potensi hambatan dan peluang untuk penerapan kurikulum yang sukses. Memahami interaksi dan pengaruh antara pembuat kebijakan, guru, orang tua, dan komunitas sangat penting untuk transisi yang lancar dari pembelajaran sebelumnya yang rusak ke pendekatan pembelajaran yang berpusat pada peserta didik. Analisis ini menyoroti bidang-bidang di mana pemangku kepentingan mungkin membutuhkan dukungan atau sumber daya tambahan untuk mengaplikasikan kurikulum baru secara efektif. Akhirnya, temuan ini dapat menginformasikan reformasi pendidikan di masa depan di Ghana. Dan konteks serupa, membuka jalan bagi pengalaman belajar yang lebih efektif dan menarik bagi semua peserta didik. Kata Kunc: layanan pendidikan Ghana; pendekatan yang berpusat pada peserta didik; keterlibatan pemangku kepentingan